Effect of smartphone location and walking speed on spatiotemporal gait parameters in older adults - Teja, Kunlanan; Lugade, Vipul; Silsupadol, Patima (Journal of Associated Medical Sciences, 2017)
Background: Cell phone use while walking has been linked with an increased number of accidental injuries. During old age, simple activities such as carrying a phone while walking may lead to gait modifications. However, no research has studied the effect of smartphone location on spatiotemporal gait parameters in older adults. Objectives: To study the effect of carrying a smartphone in 5 different locations during walking at self-selected comfortable, fast, and slow speeds on spatiotemporal gait parameters in older adults. Materials and methods: Twenty-two older adults (age 73.91±5.62 years) were asked to walk at self-selected comfortable, fast, and slow speeds over a 10-meter walkway, with the GAITRite electronic walkway placed in the middle of this path. During all walking trials, participants carried a smartphone in one of five locations: 1) in the right hand, held in a telephone speaking position (hand); 2) in the front right pant pocket (pocket); 3) on a belt attached above the front right pant pocket (belt); 4) in a shoulder bag (bag); and 5) attached to the body above the third lumbar vertebrae (body). A two-way repeated measure ANOVA was used to determine the effect of smartphone location and gait speed. The p value was set at p≤0.05. Results: No significant interaction effect was found for any spatiotemporal gait parameters. However, there was a significant main effect of smartphone location on the step length and gait speed. Specifically, when carrying a smartphone in the pocket, older adults walk with shorter step length (p=0.031) compared to the body location, and slower gait velocity compared to the bag and body locations (p=0.025 and 0.011, respectively). Conclusion: Location of smartphone affects the way older adults walk. When carrying a smartphone in the pocket, it is possible that the older adults choose a more conservative gait strategy by walking slower with a shorter step length.